ظاهرة عدم التماثل الجانبي عند الكارب الشائع((L,1758 Cyprinus carpio واستخدامها كمؤشر لتلوث المياه في بحيرة سد 16 تشرين على نهر الكبير الشمالي - حسن محمد; شمه هبه (Latakia University Journal -Biological Sciences Series, 2019)
The aim of this search was to study the fluctuating asymmetry phenomenon in common carp Cyprinus carpio and its potential usage as water pollution indicator in16th of Tishreen Lake on Alkabeer Alshimali River. A total of 113 individuals were collected from three sites (Arshwk, Alsfsaf,Alnahr alaswad) between 13/6/2016 and 11/10/2017 using gill nets and Trammel nets. Seven morphological and morphometric measurements were taken for all individuals. The results showed that the fluctuating asymmetry coefficient values for the studied traits at Arshuk and AlSafas sites were higher than those of Alnahr alaswad. These values of the preorbital distance, postorbital distance and eye diameter, were greater than the other traits in the three sites, whereas the length of head had the lowest value. Our results also showed that the value of the fluctuating asymmetry coefficient increased with the increase of total length, head length, number of lateral line scales, preorbital distance, postorbital distance, eye diameter, number of gill rakers,and eye diameter for all fish length groups in the three sites. The fact of high fluctuating asymmetry coefficient value at Arshok and Alsfsaf sites could be explained by the high organic pollutants compared to Alnahr alaswad هدف هذا البحث إلى دراسة ظاهرة عدم التماثل الجانبي عند سمك الكارب الشائع Cyprinus carpio واستخدامها كمؤشر لتلوث المياه في نهر الكبير الشمالي. جمعت العينات السمكية من ثلاثة مواقع من بحيرة سد 16 تشرين على النهر (أرشوك, الصفصاف, النهر الأسود) خلال الفترة الممتدة بين 13/6/2016و11/10/2017 باستخدام الشباك الغلصمية والشباك المبطنة, وبلغ العدد الإجمالي للأفراد المصطادة 113 فرداً سمكياً. أخذت القياسات الشكلية والقياسية لجميع الأفراد المصطادة. بينت نتائج البحث أن قيم معامل عدم التماثل الجانبي لجميع الصفات المدروسة في موقعي أرشوك والصفصاف كانت أعلى من موقع النهر الأسود. كما كان معامل عدم التماثل الجانبي للصفات الثلاث: المسافة قبل حجاج العين, المسافة بعد حجاج العين وقطر العين, أكبر من باقي الصفات المدروسة في المواقع الثلاثة, بينما أظهرت صفة طول الرأس أدنى قيمة لهذا المعامل. كما بينت النتائج أن قيمة معامل عدم التماثل الجانبي ازدادت بازدياد الطول الكلي للأفراد السمكية في المواقع الثلاثة لصفات طول الرأس, عدد حراشف الخط الجانبي, المسافة قبل حجاج العين, المسافة بعد حجاج العين, القطر الأفقي للعين, عدد الشويكات الغلصمية. يمكن أن يعزى ارتفاع معامل عدم التماثل الجانبي الكبير في موقعي أرشوك والصفصاف إلى وجود كميات عالية من الملوثات العضوية في هذين الموقعين بالمقارنة مع موقع النهر الأسود.